Arts Follies, 1953. - Frank Jones (Forsyth County Public Library, 1953)
WSJ 5-2-53 p.3.
Arts Follies. People are Earline King, Mayor Marshall Kurfees, Bonnie Frasier, and Lou Lewis.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth; Winston-Salem (N.C.)